Strategi Guru PAI dalam Memanajemen Sarana dan Prasarana Pada Pembelajaran Pendidikan Agama Islam di SMPN Bingin Teluk Kabupaten Musi Rawas Utara Provinsi Sumatera Selatan. - Emiliana; Suradi, Ahmad; Nasution, Adam (JPT : Jurnal Pendidikan Tematik, 2022)
This research is motivated by Islamic education learning needs to be supported by good facilities and infrastructure. On this basis, the formulation of the problem in this study is how the strategy of PAI teachers in Facilities and Infrastructure Management in Islamic Religious Education Learning at SMPN Bingin Teluk and what obstacles are faced by PAI teachers in Management of Facilities and Infrastructure in Islamic Religious Education Learning at SMPN Bingin Teluk . The purpose of this study is to describe how the PAI teacher strategy in Facilities and Infrastructure Management in Islamic Religious Education Learning at SMPN Bingin Teluk and to describe what obstacles are faced by PAI teachers in PAI teacher strategy in Facilities and Infrastructure Management in Islamic Religious Education Learning at SMPN Bingin Bay. This type of research is field research with a qualitative descriptive approach. The results of the study concluded that the PAI teacher's strategy in managing facilities and infrastructure in Islamic Religious Education learning at SMP Negeri Bingin Teluk includes planning, namely preparing facilities and infrastructure used in the learning process, assessing the feasibility of facilities and infrastructure, mapping facilities and infrastructure by taking into account conditions. school funding, making preparations so that there are no obstacles when learning. Furthermore, in the implementation of learning the teacher shows a warm and enthusiastic attitude by showing concern and familiarity to students and giving rewards to students, using media that are in accordance with the material presented, varying teaching methods and carrying out assessments at the end of learning. Obstacles faced by PAI teachers in the management of facilities and infrastructure in Islamic Religious Education learning at SMPN Bingin Teluk such as old facilities and infrastructure, some have been damaged so that when they want to practice they experience obstacles. funding problems, limited location and space, and the lack of experts who handle the administration of educational facilities and infrastructure.